PEMODELAN POTENSI BENCANA BANJIR BERDASARKAN PERUBAHAN PENGGUNAAN LAHAN DI DAS WANGGU - Alamsyah, Ryan (Universitas Nusa Cendana, 2025)
High rainfall and changes in land use to built-up areas in the Wanggu watershed have reduced the soil's ability to absorb water and increased surface runoff, potentially causing flooding. This study aims to identify land use changes in 2014 and 2022, predict conditions in 2030, and analyze flood potential in these three periods using overlay methods and the Land Change Modeler. The results show that forest land experienced the largest decrease in 2014–2022, amounting to 2,048.30 ha, and is predicted to decrease again by 1,591.85 ha by 2030. Conversely, the smallest changes occurred in water bodies and plantations. Flood potential in 2014 was dominated by the no potential category, while in 2022 it shifted to the low category. Predictions for 2030 show the greatest flood potential in the moderate category, while the very high category has the smallest area coverage. These findings confirm that land use dynamics have a significant influence on increasing flood risk.